2019
DOI: 10.1111/imb.12586
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar protein sorting 4 is required for silkworm metamorphosis

Abstract: Vacuolar protein sorting 4 (Vps4) not only functions with its positive regulator vacuolar protein sorting 20‐associated 1 (Vta1) in the multivesicular body (MVB) pathway but also participates alone in MVB‐unrelated cellular processes. However, its physiological roles at the organism level remain rarely explored. We previously identified their respective homologues Bombyx mori Vps4 (BmVps4) and BmVta1 from the silkworm, a model organism for insect research. In this study, we performed fluorescence quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…RNA interference technology has also been applied in silkworm research (Xia et al, 2017, 2019; Wang & Wu, 2020). Yu et al (2016) have shown that the expression of BmD6DES was the highest at low temperature (0°C) and 6–36 h after fungal infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA interference technology has also been applied in silkworm research (Xia et al, 2017, 2019; Wang & Wu, 2020). Yu et al (2016) have shown that the expression of BmD6DES was the highest at low temperature (0°C) and 6–36 h after fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…The glycolysis pathway is an important energy metabolism pathway in the body, PGM can convert glucose 1-phosphate into glucose 6-phosphate, which provides a raw material for the glycolysis pathway (Kim et al, 2003;Tsukamoto et al, 2013). In RNA interference technology has also been applied in silkworm research (Xia et al, 2017(Xia et al, , 2019Wang & Wu, 2020). Yu et al (2016) have shown that the expression of BmD6DES was the highest at low temperature (0°C) and 6-36 h after fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Correlational research indicated that beyond MVB formation and endocytosis, ESCRT complexes have crucial functions in cytokinesis, and mitophagy [ 18 21 ]. Knocking down BmVps4 resulted in silkworm metamorphosis reduction, including inhibiting silk gland growth, shortening spinning time, prolonging pupation, reducing the pupal size, and weight [ 22 ]. According to results of the bioinformatics analysis, BmVps13d belongs to this signal pathway and may have a similar function with BmVps4 in B .…”
Section: Discussionmentioning
confidence: 99%
“…Although RNAi success rate is low in several insect species, including silkworm, in the present study, application of RNAi efficiently suppressed silkworm U-shaped in larvae. Previously, this method has also been proved successful to knockdown partial genes, such as Vps4 (Xia et al, 2019), Kr-h1 (Zhu et al, 2020) and SGF1 (Liu et al, 2016). Recently, You et al (2020) improved the RNAi susceptibility of silkworm larvae by overexpressing RNAi's core machinery .…”
Section: Discussionmentioning
confidence: 99%